Comparison of Growth Traits of Male Bali Cattle (Bos javanicus) with Different Adult Coat Colors - Suhendro, I.; Jakaria, J.; Priyanto, R.; Manalu, W.; Hartono, S.; Noor, R. R. (Faculty of Animal Science, IPB University, 2024)
Bali cattle have a distinct coloration that indicates the sexual dimorphism of adult cattle. However, coat color deviations are found in bulls due to either genetic impurity or inbreeding. Furthermore, information is needed to determine whether there is a relationship between coat color and cattle performance. This study aimed to evaluate the potential association between coat color deviation and the growth traits of male Bali cattle. A total of 99 adult male Bali cattle from Livestock Breeding and Forage Centre (BPTU) Denpasar, Bali, were used in this study to assess the possible association between coat color and growth capacity. Animals were grouped according to color patterns into full black (FBL), faded black (FDB), black sorel (BSR), and sorel (SRL). Periodically, growth traits of body weight (BW), wither height (WH), body length (BL), and chest circumference (CC) were measured at birth, weaning, and 365 and 730 days of age. The repeated measurement Anova analysis was used to evaluate the relation between coat color and growth traits over time. This study showed no correlation for both traits in calves due to the absence of color deviation in age. However, it turned out to be a significantly positive correlation (p<0.05) when Bali cattle reached puberty at 365 and 730 days. The black adult bulls (FBL & FDB) were significantly larger in growth traits (p<0.05) than their brown (BSR and SRL) counterparts. The coat color of male adult Bali cattle was associated with their growth traits.